Integration of Digital Technology in Islamic Education to Strengthen Muslim Epistemology and Human Resources - Fajirul Aflah; Nunu Burhanuddin; Zulfan Taufik (IQRO: Journal of Islamic Education, 2025)
The integration of digital technology within the Islamic education ecosystem faces a substantive challenge: the dominance of a pragmatic-instrumental approach that often overlooks the foundational values and epistemology of Islam. This gap risks eroding education's holistic function as a process of tarbiyah and ta'dib. This research aims to construct an integrative epistemological framework to bridge this dichotomy, ensuring digital transformation aligns with Islamic ethical and epistemic frameworks. The method employed is a critical integrative literature review, which critically synthesizes Western critical theories—such as surveillance capitalism and algorithmic governmentality—with foundational Islamic epistemic paradigms, namely Maqāṣid al-Sharī'ah and the Bayani-Burhani-Irfani trilogy. The study successfully formulates an intermethodological model that connects these two intellectual traditions. This model generates operational guiding principles, such as Digital Data as Amanah (trust) and Holistic Anti-Reductionism, designed to mitigate the risks of student data commodification and the reduction of educational goals to mere quantitative indicators. The research concludes that a value-based digital integration, grounded in this epistemic synthesis, is not merely important but essential for cultivating contemporary, excellent Muslim human resources: those who are proficient and critical in digital spaces (digital proficient), sovereign in thinking and knowledge acquisition (epistemically sovereign), and possess spiritual and moral resilience (spiritually resilient) amidst the currents of modernity.